Features of the Regional Economic Systems Development with a Mono-Branch Focus - O. V. Astafyeva; E. V. Astafyev (Управленческие науки)
Subject. The relevance of the study is explained by the need to develop regional economic systems based on the activation of innovative processes and the use of a differentiated approach depending on the level of economic development of the territory.The subject of this study is the regions of the national economy, characterized by a strong branch orientation.Purpose. The author of the article attempts to develop an approach to ensure innovative development of economy on the basis of determining the strategic direction of regions development with an industry focus, by targeting the key parameters of the system. Within the framework of the stated goal solution, the method of analytical hierarchical procedure was used, allowing to decompose the investigated problem and to carry out a paired comparison of the selected development strategies.Methodology. A grouping of indicators was carried out, the dynamics of which can be used to determine the stage of the industry life cycle, dominating in the region. Three strategic vectors of the region development were identified, taking into account the dynamics of innovative processes in the industry and contribution to the region economic development which is dominant in the economic activity, the indicators determining the stage of the industry life cycle were pointed out, the approach to identify strategic development priorities of the regional economy was proposed taking into account the most important factors. There is an approach to the prioritization of regional economic systems development strategies with paired comparisons of alternatives.Results. The calculations allow choosing development strategies for the regional economy development with a mono-branch focus depending on the relative importance of the selected criteria.Conclusions. The formulated provisions can be taken into account in the development of the strategy of the regional economy advanced development by enhancing innovative activity.